(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Objectives: To study the clinical presentation and risk factors of persistent trophoblastic disease and its outcome of treatment with chemotherapy. Materials and methods: This observational study was carried out on fifty patients of persistent trophoblastic disease who were admitted in the Department of Obstetrics & Gynaecology, Mymensingh Medical Hospital (MMCH) during one year period. Evaluation of disease was done by thorough clinical examination and a set of investigations including chest radiography, ultrasound scan of abdomen and pelvis and estimation of serum â hCG. The four factors under analysis of PTD were age of the patient, clinical presentation, gestational age at diagnosis of molar pregnancy and nature of antecedent pregnancy. Patients with non-metastatic trophoblastic disease and low risk metastatic trophoblastic disease were offered single agent chemotherapy with methotrexate and folinic acid rescue in consultation with the oncologist. When â hCG response was inadequate, multi-agent chemotherapy was given. Complications of chemotherapy were also observed and supportive treatment was given. Results: Out of 50 patients, 49 (98%) patients had antecedent molar pregnancy and 1(2%) had missed abortion. In cases of post molar trophoblastic disease, 28 (57.58%) were in 20-30 yrs. Mean ± SD was 31.35 ± 7.25. In these cases gestational size of molar pregnancy was between 16-20 weeks in 24 (48.98%), <16 wks in 19 (38.78%) and >20 wks in 6 (12.24%) cases. Mean ± SD was 16.78 ± 4.45 wks (p<0.001). Associated theca lutein cysts were present among higher number of cases (57.14%) but not statistically significant. Regarding clinical presentation, 40 (80%) patients presented with irregular pervaginal bleeding, 3(6%) patients with features of metastasis. Most of the of the study subjects 43 (86%) were treated with chemotherapy and 7 (14%) had undergone both hysterectomy and chemotherapy. Single agent methotrexate was given in 47 (94%) cases and multiple agent (EMA-CO) in 3 (6%). After giving 4 cycles of chemotherapy 11 (22%) patients were cured, 38 (76%) had declining â hCG level and one had static â hCG level. Overall remission was 98 %. Complication of chemotherapy was observed in 5 (10%) patients. Conclusion: Theca lutein cyst are important in the prediction of persistent disease after molar pregnancy. Methotrexate chemotherapy is effective and well tolerated in treating patients with nonmetastatic and low risk metastatic gestational trophoblastic neoplasia. Bangladesh J Obstet Gynaecol, 2012; Vol. 27(2) : 50-56